Vulvovaginitis as a Risk Factor for the Degree of Labial Adhesions in Prepubertal Girls with Labial Fusion - Efthimios, Deligeoroglou; Vasileios, Karountzos; Konstantinos, D. Dimopoulos; Nikolaos, Athanasopoulos; Pandelis, Tsimaris (Journal of Women's Reproductive Health, 2017)
Objectives: The aim of this study is to assess the correlation between the degree (percentage) of occlusion due to labial adhesions and vulvovaginitis. Materials and Methods: Prospective study of pre-pubertal females who attended our Division, during the past 7 years, due to labial fusion. Medical history, clinical examination and Q tip culture of vaginal fluid samples were performed, after separation of the labia. Treatment of isolated pathogens was administered, based on antibiogram results. Results: 53 patients, with mean age 3.81 years (±0.88 years, SD:2.65, range:0.33-9.5 years) had a total of 89 vaginal specimens collected, as re-culture was performed in 17 patients due to labial fusion recurrence. In 32.08% no pathogen was isolated. Gardnerella vaginalis (24.51%) and Bacteroides spp (15.09%) were the commonest isolated pathogens of the rest 67.92%. Among labial fusion recurrences the commonest isolated pathogen was Gardnerella vaginalis (23.13%), while in 36.12% no specific pathogen was detected. Conclusions: The results suggest that non-specific vulvovaginitis is responsible for lower degree (<60% closure) of labial adhesions, as well as that recurrent infection plays a role in the formation of higher degree/percentage of labial closure, especially when there are one or more pathogens present. Furthermore, the presence of anaerobes at initial cultures, together with Gram negative bacteria at re-cultures, appear to further facilitate the creation of extensive adhesions.
Keywords: Labial adhesions; pathogens; vulvovaginitis; prepubertal